Transcription factor expression is the main determinant of variability in gene co‐activity - Lucas van Duin; Robert Krautz; Sarah Rennie; Robin Andersson (Molecular Systems Biology)
Abstract Many genes are co‐expressed and form genomic domains of coordinated gene activity. However, the regulatory determinants of domain co‐activity remain unclear. Here, we leverage human individual variation in gene expression to characterize the co‐regulatory processes underlying domain co‐activity and systematically quantify their effect sizes. We employ transcriptional decomposition to extract from RNA expression data an expression component related to co‐activity revealed by genomic positioning. This strategy reveals close to 1,500 co‐activity domains, covering most expressed genes, of which the large majority are invariable across individuals. Focusing specifically on domains with high variability in co‐activity reveals that contained genes have a higher sharing of eQTLs, a higher variability in enhancer interactions, and an enrichment of binding by variably expressed transcription factors, compared to genes within non‐variable domains. Through careful quantification of the relative contributions of regulatory processes underlying co‐activity, we find transcription factor expression levels to be the main determinant of gene co‐activity. Our results indicate that distal trans effects contribute more than local genetic variation to individual variation in co‐activity domains.